Aqueous Light‐Controlled Self‐Assembly of Nanoparticles. Issue 9 (23rd June 2016) - Samanta, Dipak; Klajn, Rafal
Abstract : Come on in, the water's fine! Non‐photoresponsive nanoparticles can be reversibly assembled using light by placing them in an aqueous solution of a photoacid. Upon exposure to visible light, the photoacid reduces the pH of the solution, which induces attractive interactions between the nanoparticles. In the dark, the resulting nanoparticle aggregates spontaneously disassemble. The process can be repeated many times.